The Effect of the Peer-Review Technique on Students’ Writing Ability - Martin Kustati; Yuhardi Yuhardi (Studies in English Language and Education, 2014)
The  aim of this  study  was  to investigate  if  there could be a  significant positive effect by using Peer-Review Technique (PRT) on students‟ ability in writing  English. An experimental research  method  was used in this study. A writing test based on the indicators of Jacobs et al. (1981) was completed by 65  undergraduate  students  in  English  from  the  English Department  at  the Faculty  of Education and Teacher Training in the  State Institute for Islamic Studies “Imam Bonjol‟  at  Padang.  The students  were divided into two groups:  an  experimental group (n=33) and  a  control group (n=32). Both groups  were similar in terms of academic level,  the  given writing task and their  target language  [English]   proficiency. The experimental participants were introduced to  Peer-Review  Technique in  essay writing sessions whilst the control group participants were taught through the teacher’s traditional feedback (TTF) whereby  students worked individually to produce their texts. The findings  showed that PRT gave  a  significant  improvement  effect on  the students‟ writing abilities. This study is expected to serve as (1)  data  for further  developing PRT; (2) input for  lecturers  in  writing  to  develop more effective and innovative learning; and (3)  additional  material  for  the development of critical and cooperative learning theories in teaching writing.